2020
DOI: 10.1002/adfm.201910402
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Tumor Biology and Targeted Nanoplatforms for Imaging Applications

Abstract: Although considerable efforts have been conducted to diagnose, improve, and treat cancer in the past few decades, existing therapeutic options are insufficient, as mortality and morbidity rates remain high. Perhaps the best hope for substantial improvement lies in early detection. Recent advances in nanotechnology are expected to increase the current understanding of tumor biology, and will allow nanomaterials to be used for targeting and imaging both in vitro and in vivo experimental models. Owing to their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 347 publications
(254 reference statements)
0
19
0
Order By: Relevance
“…Let's also assume that the bond is under a force load, defined as f B , that will act to accelerate bond rupture. The observed kinetic reverse reaction rate, k r , can be expressed in terms of the intrinsic value, k o r , and f B , as follows: (6)…”
Section: Bond Biophysicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let's also assume that the bond is under a force load, defined as f B , that will act to accelerate bond rupture. The observed kinetic reverse reaction rate, k r , can be expressed in terms of the intrinsic value, k o r , and f B , as follows: (6)…”
Section: Bond Biophysicsmentioning
confidence: 99%
“…Recent reviews have highlighted various NP strategies aimed at enhancing imaging for diagnosis and drug efficacy for therapy [ 4 , 5 ]. Compared to alternative clinical contrast agents, NPs tend to exhibit higher sensitivity and/or specificity for abnormalities such as tumors due to selective delivery [ 6 ], including preclinical studies that have shown promise for computed tomography, magnetic resonance imaging, ultrasound, and positron emission tomography (see reviews: [ 7 , 8 ]). However, only a few NP imaging agents have been approved for clinical use [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Active targeting of nanomaterials has been covered in most recent reviews, including various tumor‐specific targeting locations (tumor microenvironment, tumor neo‐vasculature, and cancer cells) along with corresponding active targeting strategies, and several targeting ligands (Azizi et al, 2020; Mi, Cabral, & Kataoka, 2020). One of the major advantages of the dendritic nano‐scale system in the design of tumor active targeting is their high density and the availability of multiple terminal groups.…”
Section: Design Strategies For Dendritic Nano‐scale Systems For Cancementioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer worldwide and the second leading cause of cancer death (Azizi et al, 2020). Globally, approximately 1.8 million cases were diagnosed in 2018 (Azizi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer worldwide and the second leading cause of cancer death (Azizi et al, 2020). Globally, approximately 1.8 million cases were diagnosed in 2018 (Azizi et al, 2020). In the United States, it is estimated that nearly 150,000 new cases are diagnosed as CRC and 52,000 people die each year (O'Leary et al, 2020).…”
Section: Introductionmentioning
confidence: 99%